The Role of Knowledge-Sharing Mediation and its Impact Between Organizational Justice and Innovative Work Behavior - ., Mudiono; Tjahjono, Heru Kurnianto; Qamari, Ika Nurul (Journal of Ecohumanism, 2024)
This study explores the impact of organizational justice on teachers’ innovative work behavior in Yogyakarta’s religious education sector. The research methodology employed in this study is quantitative, which is utilized to ascertain the correlation between independent and dependent variables. We used a survey instrument comprising 372 participants. Researchers utilize Structural Equation Modeling (SEM), or Analysis of Covariance Structures, and causal modeling to test the hypothesis using the AMOS tool to analyze the Moment of Structures. The findings indicate that distributive and informational justice positively influence innovative behavior, although procedural and interpersonal justice do not. Distributive and interpersonal justice are important factors that influence knowledge-sharing among teachers. Knowledge sharing has been demonstrated to facilitate innovative work behavior, mediating between distributive justice and innovative work behavior. The results highlight the significance of organizational justice and information sharing in promoting innovation in the religious education setting in Yogyakarta. Distributional and informational justice significantly impact innovative work behavior, although procedural and interpersonal justice does not play a significant role.